Regulasi Diri Belajar Online Dimasa Pandemi Covid-19 - Kholisna, Titin; Fatimah, Siti (Nusantara of Research : Jurnal Hasil-hasil Penelitian Universitas Nusantara PGRI Kediri, 2022)
Self-regulation online learning (SRoL) is an internally proactive process for students to achieve online lectures during the Covid-19 pandemic. The purpose of this study was to describe the conditions of student lectures during the pandemic that changed their learning regulations and how the achievements were. This research method uses a descriptive quantitative approach by taking random sampling techniques on students who are active in online lectures. The description of the results of this study explains that the highest achievement of the response to self-regulation online learning (SRoL) includes six indicators, namely the first goal setting shows that 57.1% of students can make learning strategies well. The second indicator of environment structuring is how they manage the environment in a conducive way, which responded to 35.7%. The third indicator of task management was responded to by 7.1%, and the fourth indicator for time management explained that 32.9% of students could manage their time. The fifth is help-seeking, namely asking for help from friends 80.1% in doing assignments or needing understanding. The sixth self-evaluation was responded to by 44.3%, namely students evaluating learning outcomes with learning outcomes. This data shows that the achievement of lectures carried out with the online system does not guarantee maximum effort even though they can access lecture assignments more easily with the internet network.